Pengaruh Kecerdasan Emosional, Komitmen Organisasional dan Organizational Citizenship Behavior terhadap Kinerja Karyawan - Fitriastuti, Triana (JDM (Jurnal Dinamika Manajemen), 2013)
The purpose of this study is to investigate the impact of Emotional Intellegent, Organizational commitment and Organizational Citizenship Behavior on employee performance. This study uses survey research design and the respondents are 89 Government Employees of industry and trade organization, located in Kutai. The sampling method used is Purposive Sampling based on some criterias. The result of multiple regression analysis shows that Emotional Intellegent, organizational commitment and OCB have positive impact on employee performance. The result of study shows that employees who have emotional intelligent will work better based on organization standard and they will have better performance. It is also needed employees with high comitment for showing the optimal work so that they can contribute to the corporate. The employees who behave based on OCB, will indirectly influence the achievement of corporate goals since they will contribute to the increase of employee performance.